Phaeochromocytoma in Nepal – A Single Centre Experience - Maskey, Pukar; Shrestha, GK; Luitel, BR; Gupta, DK; Sidarth, -; Chalise, PR; Sharma, UK; Gyawali, PR; Joshi, BR (Kathmandu University Medical Journal, 2013)
Background Phaeochromocytomas are rare tumors of chromaffin cells of neural crest that classically present with symptoms of catecholamine excess such as palpitations, headache and sweating. They are diagnosed by measuring plasma or urinary levels of catecholamines or their metabolites. Anatomic localization is done by computed tomographic scan or magnetic resonance imaging, or meta-iodobenzyl guanidine scan in certain cases. Adequate preoperative catecholamine blockade prevents perioperative hemodynamic instability. Objectives To study the clinical spectrum and management of phaeochromocytomas in a tertiary care centre, Tribhuvan University Teaching Hospital, in Nepal. Methods Retrospective review of case records of histologically proven cases of phaeochromocytomas from 2008 -2011 was done, and data collected on clinical spectrum, diagnostic modalities, perioperative management and follow-up. Results Tweleve cases of phaeochromocytomas were operated. The mean age was 36.41±14.07 years. There were 2 bilateral phaeochromocytomas and 1 extra-adrenal paraganglioma. Apart from the common symptoms of catecholamine excess, patients had atypical presentations like psychiatric manifestations and blurred vision. A combination of urinary Vanillyl Mandelic Acid and computed tomographic scan was used for diagnosis, and open surgery was done in all cases. Pre-operative blood pressure control was achieved by prazocin or calcium channel blockers. Ten patients had intraoperative surge in blood pressure. There were no major morbidity or mortality. Three patients had high blood pressure post-operatively, but were effectively managed with antihypertensives. Conclusion Phaeochromocytomas can have variable presentation. Good preoperative preparation and perioperative management can result in an excellent outcome. Kathmandu University Medical Journal | VOL.10 | NO. 3 | ISSUE 39 | JUL- SEP 2012 | Page 52-55 DOI: http://dx.doi.org/10.3126/kumj.v10i3.8020